Design of tariff schemes as demand response mechanisms for stand-alone microgrids planning. (15th November 2020) - Oviedo-Cepeda, J.C.; Serna-Suárez, Ivan; Osma-Pinto, German; Duarte, Cesar; Solano, Javier; Gabbar, Hossam A.
Abstract: Stand Alone Microgrids provide electric energy to isolated communities when the grid's extension is not feasible. However, Stand Alone Microgrids face technical, financial, and regulatory challenges before reaching most rural populations. This paper explores how energy tariffs and public subsidies for rural electrification are related to the optimal operation and design of Stand Alone Microgrids. It aims to propose a holistic methodology to determine the optimal sizing, optimal energy management, optimal tariffs, and public subsidies for Stand Alone Microgrids using Disciplined Convex Programming. The study guarantees the convexity of the proposed formulation and the uniqueness of the optimal solution by following the rules of Disciplined Convex Programming. A case study shows a non-negligible impact of time-varying tariffs over the sizing, energy management, and fuel consumption. Compared with flat tariffs, using a variable tariff reduces costumers' payments up to 21% and diesel consumption of 11%. However, investor profits can be reduced by up to 18%. In this regard, the study reveals and propose a solution to the challenge that governments and policymakers face trying to define tariffs to attract private investors interest in funding rural electrification projects on one side, and create fair tariffs for the customers on the other side. Highlights: A sizing approach that integrates optimal energy dispatch and tariff design. Tariffs impact measurement over the private investments and customer payments. Definition of public investments to prevent excess profits for private investors.